2021
DOI: 10.1016/j.xkme.2021.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Improving Access to Kidney Transplantation: Perspectives From Dialysis and Transplant Staff in the Southeastern United States

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 18 publications
1
21
0
5
Order By: Relevance
“…Thus, the marital relationship can be a protective factor in the access to information and in the health care of men. In addition, with the event of the transplant, families face the impact of the entire process, including the fact that their members stop carrying out their professional activities, as well as the children's school dropout, which directly impacts the routine and family organization (12)(13)(14)(15)20) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the marital relationship can be a protective factor in the access to information and in the health care of men. In addition, with the event of the transplant, families face the impact of the entire process, including the fact that their members stop carrying out their professional activities, as well as the children's school dropout, which directly impacts the routine and family organization (12)(13)(14)(15)20) .…”
Section: Discussionmentioning
confidence: 99%
“…It is known that CKD is related to socially defined factors such as population with low socioeconomic status, in social vulnerability and ethnic minorities. These groups face the coexistence of communicable and noncommunicable diseases, as well as the difficulty of initiating treatment in one of the RRTs (13)(14)(15)(16) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of comparing absolute effects between race categories, we identified that over half of the patients in all‐race hot spots were Hispanic (52%), while nearly one‐third (28%) were NHB, suggesting substantial racial inequities within the geographic disparities we identified. Policy changes and interventions, such as improving patient education on transplantation, standardizing patient referral, mandating universal transportation options for patients at transplant centers, and standardizing transplant eligibility across transplant centers may be viable solutions for reducing racial disparities 31–34 …”
Section: Discussionmentioning
confidence: 99%
“…Policy changes and interventions, such as improving patient education on transplantation, standardizing patient referral, mandating universal transportation options for patients at transplant centers, and standardizing transplant eligibility across transplant centers may be viable solutions for reducing racial disparities. [31][32][33][34] Future work examining wait list disparities should consider further integration of geospatial context and methods to better account for the geographic disparities identified in this work. Beyond wait-listing, the geographic clustering methods utilized in this study can be translated not only to other KT disparities, but also within wider organ transplant disparity studies.…”
Section: Discussionmentioning
confidence: 99%